2002
DOI: 10.1136/gut.50.3.295
|View full text |Cite
|
Sign up to set email alerts
|

Evidence that cagA+Helicobacter pylori strains are disappearing more rapidly than cagA- strains

Abstract: Background and aims: The prevalence of Helicobacter pylori colonisation in populations in developed country has been declining, as shown by community based serological surveys of adults in Vammala, Finland in 1973 and1994. In this study, we determined whether the proportion of subjects colonised by cagA + or cagA − H pylori strains has changed as the overall prevalence of H pylori + has declined. Methods: We examined 911 sera from Vammala's study for antibodies to the CagA antigen of H pylori using a truncated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
73
3

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(87 citation statements)
references
References 37 publications
11
73
3
Order By: Relevance
“…Based on these observation it seems that colonization of some younger subjects (< 30 years) with CagA-positive strains is a transient phenomenon. The accumulating evidence regarding CagA-positive strains are more susceptible than CagA-negative strains to eradication treatment [33] is consistent with our observation. Our result showed that the prevalence of anti-H pylori antibody was significantly higher in males compared to females.…”
Section: Discussionsupporting
confidence: 92%
“…Based on these observation it seems that colonization of some younger subjects (< 30 years) with CagA-positive strains is a transient phenomenon. The accumulating evidence regarding CagA-positive strains are more susceptible than CagA-negative strains to eradication treatment [33] is consistent with our observation. Our result showed that the prevalence of anti-H pylori antibody was significantly higher in males compared to females.…”
Section: Discussionsupporting
confidence: 92%
“…As Hp infection persists over a lifetime, it is mandatory that both the microbe and the host adapt to each other. Once chronicity is established, the immune stimulation appears remarkably constant, as antibody titers remain stable for over 20 years (36), consistent with a model of dynamic equilibrium (37). Previous studies have shown that human bronchial mucosa explants exposed to TNF-α had an increased expression of several glycosyltransferases, namely fucosyltransferases and sialyltransferases (19).…”
Section: Discussionsupporting
confidence: 81%
“…The proportion of young children becoming infected is now extremely low, most probably due to antibiotic use [18]. Puzzlingly, there has also been a selective decline in the more virulent CagA + strains of H. pylori [19]. In opposition to this, between 1973 and 1994, Kosunen et al [20] found that markers of allergy increased by more than threefold, with the increase mainly occurring in H. pylori-negative subjects [20].…”
Section: Introductionmentioning
confidence: 99%